Reassessing Inequality in India: A Contemporary Sociological review - Mohsin Hassan Hajam; Indira Priyadarshini (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
India, as one of the fastest-growing economies, also remains one of the most unequal societies. Over the past three decades, economic inequality has widened significantly, with the wealthiest individuals accumulating wealth at an unprecedented rate while marginalized communities continue to struggle for fair wages, quality education, and healthcare. This growing disparity disproportionately impacts women and children, exacerbating social vulnerabilities. The Time to Care report, released before the 50th annual meeting of the World Economic Forum (WEF), highlights that the wealthiest 1% of India’s population holds four times more wealth than 70% (approximately 950 million people) of the population. Furthermore, the global billionaire count has doubled in the past decade, intensifying socioeconomic divisions. Gender inequality, a critical dimension of this disparity, is evident in political representation, economic participation, and healthcare access. Reports indicate a consistent decline in India’s gender equality rankings: 108th among 153 countries in 2019, 112th in 2020, 140th in 2021, 135th in 2022, 127th in 2023, and 129th in 2024. This growing inequality, particularly gender-based disparities, raises significant sociological concerns. This article, therefore, offers a sociological analysis of economic, gender, education and Healthcare inequality in India, structured into these key discussions.